The Effect of Transfer Pricing on Tax Aggressiveness with Corporate Governance as a Moderator in Manufacturing Companies Listed on the Indonesia Stock Exchange from 2021 to 2023 - Kaisha, Lusiana; Juliana, Christina (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study analyzes the impact of transfer pricing on corporate tax aggressiveness with corporate governance as a moderating variable. The background of this study is the increasing practice of transfer pricing in multinational companies, which has an impact on tax avoidance and harms state revenue. This study uses the Joint Effects Model with Feasible Generalized Least Squares (FGLS) estimator and cross-sectional weights (PCSE) to address violations of classical assumptions. This study analyzes 127 observations from 43 companies listed on the Indonesia Stock Exchange during the period 2021-2023. The results show that transfer pricing has a positive and significant effect on tax aggressiveness at the 10% significance level, while corporate governance does not have a significant direct effect. However, the interaction between transfer pricing and good corporate governance shows a significant negative effect, meaning that the implementation of good corporate governance can reduce the positive impact of transfer pricing on tax aggressiveness. These findings emphasize the importance of strengthening good corporate governance to control risky transfer pricing practices and their implications for taxation policy.